Exploring the Relationship between Globalization and Economic Growth in Selected Countries of Middle East - Nasim Masoudi; Nazar Dahmarde; Marziye Esfandiyari (International Journal of Economics and Financial Issues, 2017)
Globalization is a social process in which geographic constraints on social and cultural relations disappear and people are increasingly aware of reduction in them. In this regard, two hypotheses are presented: efficiency hypothesis argues that globalization of the economy reduces administration tasks and makes economic conditions more competitive by more presence of private sector. In contrast, compensation hypothesis argues that globalization of the economy is a risk to society and national economy. The urgent need for energy in the twenty-first century has intensified competition among natural resources, including hydrocarbons, oil and gas. Therefore, in this study we attempted to use data from oil-rich countries of Persian Gulf to examine the relationship between globalization and economic growth. Examining the results of study using panel data method showed that in Iran there is a direct and significant correlation between the index of globalization and economic growth. This relationship doesn’t exist in other countries of the region. In fact, based on this result we can say that in Iran, the more we go toward globalization, economic growth increases. However, this globalization may be a tenth of other countries. Keywords: globalization, economic growth, comparison of the countries in the region JEL Classifications: F43, F6, F62